2021
DOI: 10.1021/acs.jpcc.1c05015
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Equilibrium of Binary Nanocrystal Superlattices

Abstract: We present a detailed investigation of nanoparticle binary superlattices. We characterize the properties of given superlattices and characterize the splayed ligand conformation, that is, vortices that determine bonding among nanoparticles. We show that the overall structure is accurately predicted by the orbifold topological model (OTM). Our explicit free energy calculations show that binary superlattices reported in experiments are dominated by many-body effects and are marginally stable or unstable, with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
(76 reference statements)
2
17
0
Order By: Relevance
“…The spherical NC we considered is Au 4033 (SC 18 ) 533 . The core diameter is D = 5.452 (nm) and from eq 12 (n = 18) it is L = 2.28 nm, 19 so that λ = 0.836. The grafting density was such that ξ = 0.85.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The spherical NC we considered is Au 4033 (SC 18 ) 533 . The core diameter is D = 5.452 (nm) and from eq 12 (n = 18) it is L = 2.28 nm, 19 so that λ = 0.836. The grafting density was such that ξ = 0.85.…”
Section: Methodsmentioning
confidence: 99%
“…16 Lattice free energies were calculated following our previous work. 17,19 Basically, the nearest neighbors are connected by harmonic springs and the reversible work is calculated by quasistatically compressing the system; see the Supporting Information for explicit formulas. In all cases, rotation of NC cores were not allowed, implemented in HOOMD-blue by including rotation false in the rigid body degrees of freedom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effective interactions are computed from fully atomistic molecular simulations of nanoparticles. In this regard there have been a number of studies previously reported [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] that have computed effective inter-particle interactions. These studies looked at various aspects of interactions between nanoparticles including length of ligand chains, role of solvent, three-body interactions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Travesset 16,17 developed the Orbifold Topological Model (OTM) that has improved upon both OPM and OCM. The predictions of the OTM were shown to be quite accurate for Binary Nanocrystal Superlattices (BNSLs) by Zha and Travesset 18 .…”
Section: Introductionmentioning
confidence: 99%